Factors effecting export trends in Uzbekistan - HALMURZAEV, Alisher (KDI School, 2015)
Research estimated the impacts of external (income levels in trading partners, world prices) and internal (production and domestic consumption of exported goods, exchange rates etc.) factors on changes in total and componential exports of Uzbekistan for the period of 1998-2009 using quarterly data. The research developed a methodology for quantifying the impact of both external and internal factors on the both aggregate and key product exports of the country. Empirical specification of the model under the study revealed important information about the sensitivities of external trade variables to internal and external factors. Findings did not reject the hypothesis set – that external factors predominantly explained changes in exports of Uzbekistan. Specifically, changes in the world price levels were the most influential factor in case of total exports as well as its key components: cotton, food, metals and energy. On the other hand, changes in exports of machinery and food have been most responsive to changes in income levels of trading partners. Even though internal monetary policies regarding foreign exchange rates had statistically negligible impacton the changes in exports of machinery, energy, metals and cotton overallimpact of real effective exchange rate on total exports was found to be both empirically and economically significant.
Thesis(Master) --KDI School:Master of Development Policy,2015